Evaluation of stereotactic radiosurgery for cerebral dural arteriovenous fistulas in a multicenter international consortium - Starke, Robert M; McCarthy, David J; Chen, Ching-Jen; Kano, Hideyuki; McShane, Brendan; Lee, John; Mathieu, David; Vasas, Lucas T; Kaufmann, Anthony M; Wang, Wei Gang; Grills, Inga S; Patibandla, Mohana Rao; et al. (Journal of neurosurgery, 2020)
OBJECTIVE: In this multicenter study, the authors reviewed the results obtained in patients who underwent Gamma Knife radiosurgery (GKRS) for dural arteriovenous fistulas (dAVFs) and determined predictors of outcome. METHODS: Data from a cohort of 114 patients who underwent GKRS for cerebral dAVFs were compiled from the International Gamma Knife Research Foundation. Favorable outcome was defined as dAVF obliteration and no posttreatment hemorrhage or permanent symptomatic radiation-induced complications. Patient and dAVF characteristics were assessed to determine predictors of outcome in a multivariate logistic regression analysis; dAVF-free obliteration was calculated in a competing-risk survival analysis; and Youden indices were used to determine optimal radiosurgical dose. RESULTS: A mean margin dose of 21.8 Gy was delivered. The mean follow-up duration was 4 years (range 0.5-18 years). The overall obliteration rate was 68.4%. The postradiosurgery actuarial rates of obliteration at 3, 5, 7, and 10 years were 41.3%, 61.1%, 70.1%, and 82.0%, respectively. Post-GRKS hemorrhage occurred in 4 patients (annual risk of 0.9%). Radiation-induced imaging changes occurred in 10.4% of patients; 5.2% were symptomatic, and 3.5% had permanent deficits. Favorable outcome was achieved in 63.2% of patients. Patients with middle fossa and tentorial dAVFs (OR 2.4, p = 0.048) and those receiving a margin dose greater than 23 Gy (OR 2.6, p = 0.030) were less likely to achieve a favorable outcome. Commonly used grading scales (e.g., Borden and Cognard) were not predictive of outcome. Female sex (OR 1.7, p = 0.03), absent venous ectasia (OR 3.4, p < 0.001), and cavernous carotid location (OR 2.1, p = 0.019) were predictors of GKRS-induced dAVF obliteration. CONCLUSIONS: GKRS for cerebral dAVFs achieved obliteration and avoided permanent complications in the majority of patients. Those with cavernous carotid location and no venous ectasia were more likely to have fistula obliteration following radiosurgery. Commonly used grading scales were not reliable predictors of outcome following radiosurgery.
Keywords: senioři; SAH = subarachnoid hemorrhage; stereotactic radiosurgery; chronické poškození mozku; fistula; Neuroimaging; GKRS = Gamma Knife radiosurgery; dural; Central Nervous System Vascular Malformations; radiační poranění; C-dAVF = cavernous dAVF; výsledek terapie; Kaplan-Meier Estimate; Middle Aged; Gamma Knife; mužské pohlaví; Radiation Injuries; Kaplanův-Meierův odhad; Adult; cévní malformace centrálního nervového systému; Radiosurgery; Postoperative Complications; Follow-Up Studies; následné studie; RIC = radiation-induced complication; ženské pohlaví; Humans; Postoperative Hemorrhage; neurozobrazování; pooperační krvácení; vascular disorders; outcome; dAVF = dural arteriovenous fistula; lidé středního věku; arteriovenous; rizikové faktory; ICH = intracerebral hemorrhage; dospělí; Brain Damage, Chronic; Female; Aged; Risk Factors; CVD = cortical venous drainage; Treatment Outcome; radiochirurgie; pooperační komplikace; lidé; Male